Ceramic tile with gradient gloss effect and three-dimensional texture and preparation method thereof

By combining high-refractive index high-gloss glaze with low-refractive index matte glaze on the glaze surface of ceramic tile, combined with the difference in melting degree during firing, the problem of single gloss of ceramic tile is solved, and the natural gradient gloss and three-dimensional texture effect is achieved, and the wear resistance and stain resistance of ceramic tile is improved.

CN119954386AActive Publication Date: 2025-05-09FOSHAN CITY GANI CERAMICS CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510436943.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-05-09
Estimated Expiration
2045-04-09

AI Technical Summary

Technical Problem

The existing ceramic tiles have a single gloss, making it difficult to achieve natural gradient gloss and three-dimensional texture effects.

Method used

By combining high-refractive index high-gloss glaze with low-refractive index matte glaze on the glaze surface of ceramic tile, combining local hood and the difference in melting degree during firing, the temperature, gloss and vitrification degree can be achieved, thereby presenting a gradient gloss effect under the reflection of light.

Benefits of technology

The natural gradient luster and three-dimensional texture of the glaze of ceramic tile are realized, which enhances the visual effect and physical properties of ceramic tile, and has also improved the wear resistance and stain resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119954386A_ABST
    Figure CN119954386A_ABST
Patent Text Reader

Abstract

The invention relates to the field of architectural ceramics, and discloses a ceramic tile with a gradient gloss effect and three-dimensional textures and a preparation method thereof.The preparation method comprises the following steps that S1, green body powder is subjected to compression molding, and a green body layer is obtained; s2, applying ground coat on the surface of the green body layer to obtain a ground coat layer; s3, performing ink-jet printing on textures on the surface of the ground coat layer to obtain a pattern layer; s4, printing highlight glaze on the surface of the pattern layer to obtain a highlight glaze layer; s5, spraying matte glaze on the surface of the highlight glaze layer to obtain a matte glaze layer; s6, performing laser engraving on the matte glaze layer to obtain a three-dimensional texture; and S7, firing molding is conducted, and the ceramic tile with the gradient gloss effect and the three-dimensional texture is obtained. According to the invention, the highlight glaze with high refractive index and the matte glaze with low refractive index are compounded, and different temperature, luster and vitrification degree are realized through local covering and melting degree difference during firing, so that the fired glaze shows the effects of gradient luster and three-dimensional texture under the reflection action of light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to a ceramic tile with a gradient gloss effect and a three-dimensional texture and a preparation method thereof. Background Art

[0002] Ceramic tiles are widely favored by consumers due to their excellent performance and decorative effects, and are widely used in the construction industry and people's daily life. Ceramic tiles on the market can be roughly divided into high-gloss glazed tiles and matte glazed tiles, and the glossiness is relatively single. In the prior art, the transition effect between gloss and matte is achieved by inkjet superposition of gloss and matte inks, but it has defects such as unnatural glaze light transition, high cost, poor pattern texture layering, and lack of three-dimensionality. Therefore, research and development of ceramic tiles that can make light present a gradient gloss effect and three-dimensional texture after reflection through the glaze has become a problem that needs to be solved urgently. Summary of the invention

[0003] The main purpose of the present invention is to provide a ceramic tile with a gradient gloss effect and a three-dimensional texture and a preparation method thereof, wherein the glaze surface of the ceramic tile has a natural gradient gloss and a three-dimensional texture.

[0004] To achieve the above object, the present invention provides a method for preparing a tile with a gradient gloss effect and a three-dimensional texture, comprising the following steps: S1, pressing the green body powder into a shape, and after drying, obtaining a green body layer; S2, applying a base glaze on the surface of the green body layer to obtain a base glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4, screen printing a high-gloss glaze on the surface of the pattern layer to obtain a high-gloss glaze layer; S5, spraying matte glaze on the surface of the high-gloss glaze layer using a high-pressure glaze spray cabinet to obtain a matte glaze layer; S6, performing laser engraving on the surface of the matte glaze layer to obtain a three-dimensional texture; S7, firing and molding, that is, obtaining the ceramic tile with a gradient gloss effect and a three-dimensional texture; The raw materials for preparing the high gloss glaze in step S4 include, by weight: 28 to 40 parts of potassium feldspar, 17 to 25 parts of quartz, 8 to 15 parts of kaolin, 10 to 16 parts of high transparent frit, 2 to 4 parts of niobium pentoxide, 7 to 14 parts of dolomite, 1 to 4 parts of zirconium silicate, 1.5 to 4 parts of perlite and 2 to 4 parts of nanomaterials; The raw materials for preparing the matte glaze in step S5 include, by weight: 30 to 45 parts of high-temperature dry particles, 8 to 12 parts of medium-temperature dry particles, 6 to 15 parts of emulsifiers, 20 to 35 parts of suspending agents, 11 to 23 parts of auxiliary agents and 8 to 13 parts of water.

[0005] The present invention compounded a high-refractive-index high-gloss glaze with a low-refractive-index matte glaze, and achieved different temperatures, gloss, and vitrification degrees through local masking and differences in the degree of melting during firing, so that the fired glaze surface presents a gradient gloss effect under the reflection of light.

[0006] Preferably, the nano material is SiO2 coated TiO2 powder. The use of SiO2 coated TiO2 powder can enhance the performance of the glaze and improve the hardness and wear resistance of the glaze.

[0007] Preferably, the chemical composition of the highly transparent frit, measured in mass percentage, comprises: SiO2 60%~75%; Al2O35%~15%; B2O35%~10%; Na2O and / or K2O 10% to 20%; CaO and / or MgO 1% to 5%; ZnO 0%~5%; The chemical composition of the high-temperature dry particles, measured in mass percentage, includes: SiO250%~70%; Al2O310%~25%; B2O30%~8%; ZnO 0%~5%; ZrO20%~5%; Alkali metal oxides 2% to 10%; Alkaline earth metal oxides 5% to 15%; The chemical composition of the medium-temperature dry particles, measured in mass percentage, includes: SiO2 52%~66%; Al2O310%~12%; Na2O and / or K2O 5% to 15%; ZnO5%~7%; SrO2%~3%; Alkaline earth metal oxides 9% to 15.5%; The alkali metal oxide is at least one of Na2O, K2O and Li2O; the alkaline earth metal oxide is at least one of CaO, MgO and BaO.

[0008] Preferably, the thickness of the high-gloss glaze layer is 180-360 μm, and the refractive index of the high-gloss glaze layer is 1.68-1.72; the thickness of the matte glaze layer is 90-180 μm, and the refractive index of the matte glaze layer is 1.45-1.55. The refractive index between the high-gloss glaze layer and the matte glaze layer is adjusted, and the gloss difference formed by the different refractive indices of the two after firing is utilized, so as to achieve a good gradient gloss effect of the glaze surface.

[0009] Preferably, the opacifier includes one or both of zirconium silicate and calcium fluoride. Zirconium silicate can form microcrystals or incompletely melted particles to scatter light, reducing the gloss and refractive index of the glaze. Fluoride ions in calcium fluoride promote the formation of microporous structures on the glaze surface during firing, enhancing the matte effect.

[0010] Preferably, the auxiliary agent includes one or both of calcium phosphate and tetragonal alumina. Tetragonal alumina can improve the hardness and stability of the glaze layer, and calcium phosphate scatters light and reduces glossiness and refractive index.

[0011] Preferably, in step S6, a three-dimensional texture with a depth of 10 to 50 μm is engraved on the surface of the matte glaze layer. The two-dimensional texture formed by the partial misalignment and stacking of the high-refractive glaze layer and the low-refractive glaze layer, and the three-dimensional texture formed by laser engraving on the surface of the glaze layer, can enhance the three-dimensional effect of the pattern on the surface of the tile, and the texture is more realistic and restored.

[0012] Preferably, the raw materials for preparing the green body layer include, by weight: 10-15 parts of kaolin, 12-16 parts of sodium potassium stone powder, 6-11 parts of high-alumina potassium sand, 10-13 parts of sodium stone powder, 9-14 parts of potassium sand, 14-19 parts of raw ore mud, 2-5 parts of black talc, 3-8 parts of polishing waste residue, 9-14 parts of washed sand, 5-9 parts of washed mud and 0.8-1.5 parts of additives.

[0013] Preferably, in step S7, the firing temperature is 1180-1225° C., and the firing time is 55-76 min.

[0014] The present invention also provides a tile with a gradient gloss effect and a three-dimensional texture, which is prepared by the above-mentioned preparation method. The prepared tile can present a natural gradient gloss effect while ensuring durability, and the three-dimensional texture is more three-dimensional and realistic, restoring the real stone. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 The glaze effect of Example 1 Figure 1 ; Figure 2 The glaze effect of Example 1 Figure 2 .

[0017] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0019] The present invention provides a method for preparing a tile with a gradient gloss effect and a three-dimensional texture, comprising the following steps: S1. Pressing the green body powder into a shape and drying it to obtain a green body layer; preferably, the raw materials for preparing the green body layer, in parts by weight, include: 10-15 parts of kaolin, 12-16 parts of sodium potassium stone powder, 6-11 parts of high-aluminum potassium sand, 10-13 parts of sodium stone powder, 9-14 parts of potassium sand, 14-19 parts of raw ore mud, 2-5 parts of black talc, 3-8 parts of polishing waste residue, 9-14 parts of washed sand, 5-9 parts of washed mud and 0.8-1.5 parts of additives.

[0020] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Screen-printed high-gloss glaze is applied on the surface of the pattern layer, and dried in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer having a thickness of 180-360 μm and a refractive index of 1.68-1.72. Specifically, the raw materials for preparing the high-gloss glaze include, by weight: 28-40 parts of potassium feldspar, 17-25 parts of quartz, 8-15 parts of kaolin, 10-16 parts of high-transparent frit, 2-4 parts of niobium pentoxide, 7-14 parts of dolomite, 1-4 parts of zirconium silicate, 1.5-4 parts of perlite, and 2-4 parts of nanomaterials. The chemical composition of the high-transparency frit is calculated by mass percentage, including: SiO2: 60% to 75%, Al2O3: 5% to 15%, B2O3: 5% to 10%, Na2O and / or K2O: 10% to 20%, CaO and / or MgO: 1% to 5%, ZnO: 0% to 5%. It is understood that the chemical composition of the high-transparency frit includes at least one of Na2O and K2O, and the total amount accounts for 10% to 20%; similarly, the chemical composition of the high-transparency frit includes at least one of CaO and MgO, and the total amount accounts for 1% to 5%. Preferably, the nanomaterial is SiO2-coated TiO2 powder.

[0021] S5. Spray matte glaze on the surface of the high-gloss glaze layer using a high-pressure spray glaze cabinet, dry it in a drying oven at a temperature of 150°C for 1 minute, and obtain a matte glaze layer with a thickness of 90 to 180 μm and a refractive index of 1.45 to 1.55. Specifically, the raw materials for preparing the matte glaze, in parts by weight, include: 30 to 45 parts of high-temperature dry particles, 8 to 12 parts of medium-temperature dry particles, 6 to 15 parts of emulsifiers, 20 to 35 parts of suspending agents, 11 to 23 parts of auxiliary agents, and 8 to 13 parts of water. Among them, the sintering temperature of high-temperature dry particles is 30 to 40°C higher than that of medium-temperature dry particles. The chemical composition of the high-temperature dry particles, calculated by mass percentage, includes: SiO2: 50% to 70%, Al2O3: 10% to 25%, B2O3: 0% to 8%, ZnO: 0% to 5%, ZrO2: 0% to 5%, alkali metal oxides: 2% to 10%, alkaline earth metal oxides: 5% to 15%; the chemical composition of the medium-temperature dry particles, calculated by mass percentage, includes: SiO2: 52% to 66%, Al2O3: 10% to 12%, Na2O and / or K2O: 5% to 15%, ZnO: 5% to 7%, SrO: 2% to 3%, alkaline earth metal oxides: 9% to 15.5%. The alkali metal oxide is at least one of Na2O, K2O and Li2O; the alkaline earth metal oxide is at least one of CaO, MgO and BaO. It can be understood that the chemical composition of high-temperature dry particles includes at least one of Na2O, K2O and Li2O, and the total amount accounts for 2% to 10%; the chemical composition of high-temperature dry particles also includes at least one of CaO, MgO and BaO, and the total amount accounts for 5% to 15%; the chemical composition of medium-temperature dry particles includes at least one of Na2O and K2O, and the total amount accounts for 5% to 15%; the chemical composition of medium-temperature dry particles also includes at least one of CaO, MgO and BaO, and the total amount accounts for 9% to 15.5%.

[0022] Preferably, the opacifier includes one or both of zirconium silicate and calcium fluoride; the auxiliary agent includes one or both of calcium phosphate and tetragonal alumina. The suspending agent can be a well-known organic suspending agent that can be used in glaze. The suspending agent used in the following examples of this application is a dry particle suspending agent, which is a dry particle suspending agent 9022A purchased from Jiangxi Qiantao New Materials Co., Ltd.

[0023] S6. Carving a three-dimensional texture with a depth of 10 to 50 μm on the surface of the matte glaze layer. Specifically, a laser etching machine may be used to perform bionic texture carving.

[0024] S7, firing and forming, the firing temperature is 1180-1225° C., and the firing time is 55-76 minutes, so as to obtain the ceramic tile with the gradient gloss effect and three-dimensional texture.

[0025] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only an example within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not intended to be limited to the specific values ​​of the examples below. If the specific conditions are not specified in the examples, proceed according to conventional conditions or the conditions recommended by the manufacturer.

[0026] Illustratively, the raw materials of the base glaze formula in the following embodiments and comparative examples are, by mass, 25 parts of potassium feldspar, 10 parts of sodium feldspar, 22 parts of quartz, 12 parts of kaolin, 8 parts of calcite, 5 parts of talc, 3 parts of zinc oxide, 3 parts of barium carbonate, 2 parts of bentonite, and 10 parts of zirconium silicate.

[0027] In the following embodiments, the additives used in the raw materials of the green body layer are one or more of sodium tripolyphosphate, water glass, carboxymethyl cellulose (CMC), and green body plasticizer, all of which are commercially available products.

[0028] Example 1 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 13 parts of kaolin, 12 parts of potassium sodium stone powder, 8 parts of high-aluminum potassium sand, 11 parts of sodium stone powder, 10 parts of potassium sand, 16 parts of raw ore mud, 3 parts of black talc, 6 parts of polishing waste residue, 12 parts of washed sand, 8 parts of washed mud and 1 part of sodium tripolyphosphate.

[0029] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Screen-printed high-gloss glaze is applied on the surface of the pattern layer, and dried in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer with a thickness of 180 μm and a refractive index of 1.72. The raw materials for preparing the high-gloss glaze include, by weight: 28 parts of potassium feldspar, 17 parts of quartz, 15 parts of kaolin, 16 parts of high-transparent frit, 4 parts of niobium pentoxide, 14 parts of dolomite, 1 part of zirconium silicate, 2 parts of perlite and 2 parts of SiO2-coated TiO2 powder.

[0030] The chemical composition of the high-transparent frit is expressed in percentage by mass and includes: SiO2: 60%, Al2O3: 15%, B2O3: 10%, Na2O: 6%, K2O: 4%, MgO: 2%, and ZnO: 3%.

[0031] S5. Spray matte glaze on the surface of the high-gloss glaze layer using a high-pressure spray glaze cabinet, and dry it in a drying oven at a drying temperature of 150°C for 1 minute to obtain a matte glaze layer with a thickness of 90 μm and a refractive index of 1.55. The raw materials for preparing the matte glaze, in parts by weight, include: 30 parts of high-temperature dry particles, 12 parts of medium-temperature dry particles, 6 parts of zirconium silicate, 25 parts of 9022A, 19 parts of calcium phosphate, and 8 parts of water. Among them, the sintering temperature of the high-temperature dry particles is 40°C higher than that of the medium-temperature dry particles.

[0032] The chemical composition of the high temperature dry particles, in terms of mass percentage, includes: SiO2: 50%, Al2O3: 25%, B2O3: 5%, K2O: 2%, Li2O: 2%, CaO: 6%, BaO: 4%, ZnO: 3%, ZrO2: 3%; The chemical composition of the medium-temperature dry particles, in terms of mass percentage, includes: SiO2: 52%, Al2O3: 10%, Na2O: 10%, K2O: 4%, MgO: 9%, BaO: 6%, ZnO: 7%, and SrO: 2%.

[0033] S6. A laser etching machine is used to carve a three-dimensional texture with a depth of 10 μm on the surface of the matte glaze layer.

[0034] S7, firing and molding, the firing temperature is 1180° C., and the firing time is 76 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0035] Example 2 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 10 parts of kaolin, 16 parts of potassium sodium stone powder, 11 parts of high-aluminum potassium sand, 10 parts of sodium stone powder, 9 parts of potassium sand, 19 parts of raw ore mud, 2 parts of black talc, 3 parts of polishing waste residue, 14 parts of washed sand, 5 parts of washed mud and 1 part of water glass.

[0036] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Screen-printed high-gloss glaze is applied on the surface of the pattern layer, and dried in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer with a thickness of 360 μm and a refractive index of 1.68. The raw materials for preparing the high-gloss glaze include, by weight: 32 parts of potassium feldspar, 17 parts of quartz, 11 parts of kaolin, 14 parts of high-transparent frit, 4 parts of niobium pentoxide, 14 parts of dolomite, 3 parts of zirconium silicate, 2 parts of perlite and 2 parts of SiO2-coated TiO2 powder.

[0037] The chemical composition of the high-transparent frit is expressed in percentage by mass and includes: SiO2: 60%, Al2O3: 15%, B2O3: 10%, Na2O: 6%, K2O: 4%, MgO: 2%, and ZnO: 3%.

[0038] S5. Spray matte glaze on the surface of the high-gloss glaze layer using a high-pressure spray glaze cabinet, dry it in a drying oven at a temperature of 150°C for 1 minute, and obtain a matte glaze layer with a thickness of 180 μm and a refractive index of 1.45; the raw materials for preparing the matte glaze, in parts by weight, include: 45 parts of high-temperature dry particles, 8 parts of medium-temperature dry particles, 6 parts of calcium fluoride, 20 parts of 9022A, 11 parts of tetragonal alumina, and 10 parts of water. Among them, the sintering temperature of the high-temperature dry particles is 30°C higher than that of the medium-temperature dry particles.

[0039] The chemical composition of the high temperature dry particles, in terms of mass percentage, includes: SiO2: 50%, Al2O3: 25%, B2O3: 5%, K2O: 2%, Li2O: 2%, CaO: 6%, BaO: 4%, ZnO: 3%, ZrO2: 3%; The chemical composition of the medium-temperature dry particles, in terms of mass percentage, includes: SiO2: 52%, Al2O3: 10%, Na2O: 10%, K2O: 4%, MgO: 9%, BaO: 6%, ZnO: 7%, and SrO: 2%.

[0040] S6. A laser etching machine is used to carve a three-dimensional texture with a depth of 50 μm on the surface of the matte glaze layer.

[0041] S7, firing and forming, the firing temperature is 1225° C., and the firing time is 55 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0042] Example 3 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 15 parts of kaolin, 12 parts of potassium sodium stone powder, 6 parts of high-aluminum potassium sand, 12 parts of sodium stone powder, 13 parts of potassium sand, 14 parts of raw ore mud, 5 parts of black talc, 8 parts of polishing waste residue, 9 parts of washed sand, 5 parts of washed mud and 1 part of CMC.

[0043] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Screen-printed high-gloss glaze is applied on the surface of the pattern layer, and dried in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer with a thickness of 270 μm and a refractive index of 1.70. The raw materials for preparing the high-gloss glaze include, by weight: 40 parts of potassium feldspar, 17 parts of quartz, 10 parts of kaolin, 13 parts of high-transparent frit, 2 parts of niobium pentoxide, 14 parts of dolomite, 1 part of zirconium silicate, 2 parts of perlite and 4 parts of SiO2-coated TiO2 powder.

[0044] The chemical composition of the high-transparent frit is expressed in percentage by mass and includes: SiO2: 60%, Al2O3: 15%, B2O3: 10%, Na2O: 6%, K2O: 4%, MgO: 2%, and ZnO: 3%.

[0045] S5. Spray matte glaze on the surface of the high-gloss glaze layer using a high-pressure spray glaze cabinet, dry it in a drying oven at a temperature of 150°C for 1 minute, and obtain a matte glaze layer with a thickness of 130 μm and a refractive index of 1.50; the raw materials for preparing the matte glaze, in parts by weight, include: 36 parts of high-temperature dry particles, 10 parts of medium-temperature dry particles, 5 parts of zirconium silicate, 5 parts of calcium fluoride, 20 parts of 9022A, 10 parts of calcium phosphate, 5 parts of tetragonal alumina, and 9 parts of water. Among them, the sintering temperature of the high-temperature dry particles is 30°C higher than that of the medium-temperature dry particles.

[0046] The chemical composition of the high temperature dry particles, in terms of mass percentage, includes: SiO2: 50%, Al2O3: 25%, B2O3: 5%, K2O: 2%, Li2O: 2%, CaO: 6%, BaO: 4%, ZnO: 3%, ZrO2: 3%; The chemical composition of the medium-temperature dry particles, in terms of mass percentage, includes: SiO2: 52%, Al2O3: 10%, Na2O: 10%, K2O: 4%, MgO: 9%, BaO: 6%, ZnO: 7%, and SrO: 2%.

[0047] S6. A laser etching machine is used to carve a three-dimensional texture with a depth of 30 μm on the surface of the matte glaze layer.

[0048] S7, firing and forming, the firing temperature is 1200° C., and the firing time is 65 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0049] Comparative Example 1 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The raw materials for preparing the high-gloss glaze include, by weight: 28 parts of potassium feldspar, 17 parts of quartz, 15 parts of kaolin, 16 parts of high-transparent frit, 4 parts of niobium pentoxide, 14 parts of dolomite, 1 part of zirconium silicate and 2 parts of perlite.

[0050] Comparative Example 2 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The raw materials for preparing the matte glaze include, by weight, 42 parts of high-temperature dry particles, 6 parts of zirconium silicate, 25 parts of 9022A, 19 parts of calcium phosphate and 8 parts of water.

[0051] Comparative Example 3 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The raw materials for preparing the matte glaze, by weight, include: 42 parts of medium-temperature dry particles, 6 parts of zirconium silicate, 25 parts of 9022A, 19 parts of calcium phosphate and 8 parts of water.

[0052] Comparative Example 4 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The glazing thickness of the high-gloss glaze layer was adjusted to 150 μm.

[0053] Comparative Example 5 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The glazing thickness of the high-gloss glaze layer was adjusted to 400 μm.

[0054] Comparative Example 6 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The glazing thickness of the matte glaze layer was adjusted to 60 μm.

[0055] Comparative Example 7 This comparative example adopts the same preparation process and parameters as Example 1, the only difference is: The glazing thickness of the matte glaze layer was adjusted to 200 μm.

[0056] Comparative Example 8 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 13 parts of kaolin, 12 parts of potassium sodium stone powder, 8 parts of high-aluminum potassium sand, 11 parts of sodium stone powder, 10 parts of potassium sand, 16 parts of raw ore mud, 3 parts of black talc, 6 parts of polishing waste residue, 12 parts of washed sand, 8 parts of washed mud and 1 part of sodium tripolyphosphate.

[0057] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Spray matte glaze on the surface of the pattern layer using a high-pressure spray glaze cabinet, dry it in a drying oven at a temperature of 150°C for 1 minute, and obtain a matte glaze layer with a thickness of 90 μm and a refractive index of 1.55; the raw materials for preparing the matte glaze, in parts by weight, include: 30 parts of high-temperature dry particles, 12 parts of medium-temperature dry particles, 6 parts of zirconium silicate, 25 parts of 9022A, 19 parts of calcium phosphate, and 8 parts of water. Among them, the sintering temperature of the high-temperature dry particles is 40°C higher than that of the medium-temperature dry particles.

[0058] The chemical composition of the high temperature dry particles, in terms of mass percentage, includes: SiO2: 50%, Al2O3: 25%, B2O3: 5%, K2O: 2%, Li2O: 2%, CaO: 6%, BaO: 4%, ZnO: 3%, ZrO2: 3%; The chemical composition of the medium-temperature dry particles, in terms of mass percentage, includes: SiO2: 52%, Al2O3: 10%, Na2O: 10%, K2O: 4%, MgO: 9%, BaO: 6%, ZnO: 7%, and SrO: 2%.

[0059] S5. Screen-print high-gloss glaze on the surface of the matte glaze layer, and dry it in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer. The thickness of the high-gloss glaze layer is 180 μm, and the refractive index is 1.72. The raw materials for preparing the high-gloss glaze, in parts by weight, include: 28 parts of potassium feldspar, 17 parts of quartz, 15 parts of kaolin, 16 parts of high-transparent frit, 4 parts of niobium pentoxide, 14 parts of dolomite, 1 part of zirconium silicate, 2 parts of perlite and 2 parts of SiO2-coated TiO2 powder.

[0060] The chemical composition of the high-transparent frit is expressed in percentage by mass and includes: SiO2: 60%, Al2O3: 15%, B2O3: 10%, Na2O: 6%, K2O: 4%, MgO: 2%, and ZnO: 3%.

[0061] S6. A laser etching machine is used to carve a three-dimensional texture with a depth of 10 μm on the surface of the high-gloss glaze layer.

[0062] S7, firing and molding, the firing temperature is 1180° C., and the firing time is 76 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0063] Comparative Example 9 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 13 parts of kaolin, 12 parts of potassium sodium stone powder, 8 parts of high-aluminum potassium sand, 11 parts of sodium stone powder, 10 parts of potassium sand, 16 parts of raw ore mud, 3 parts of black talc, 6 parts of polishing waste residue, 12 parts of washed sand, 8 parts of washed mud and 1 part of sodium tripolyphosphate.

[0064] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Screen-printed high-gloss glaze is applied on the surface of the pattern layer, and dried in a drying oven at a temperature of 120°C for 20 seconds to obtain a high-gloss glaze layer with a thickness of 180 μm and a refractive index of 1.72. The raw materials for preparing the high-gloss glaze include, by weight: 28 parts of potassium feldspar, 17 parts of quartz, 15 parts of kaolin, 16 parts of high-transparent frit, 4 parts of niobium pentoxide, 14 parts of dolomite, 1 part of zirconium silicate, 2 parts of perlite and 2 parts of SiO2-coated TiO2 powder.

[0065] The chemical composition of the high-transparent frit is expressed in percentage by mass and includes: SiO2: 60%, Al2O3: 15%, B2O3: 10%, Na2O: 6%, K2O: 4%, MgO: 2%, and ZnO: 3%.

[0066] S5. A laser etching machine is used to carve a three-dimensional texture with a depth of 10 μm on the surface of the high-gloss glaze layer.

[0067] S6, firing and forming, the firing temperature is 1180° C., and the firing time is 76 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0068] Comparative Example 10 A method for preparing a tile with a gradient gloss effect and a three-dimensional texture comprises the following steps: S1. Press the green body powder into shape, and after drying, obtain a green body layer; the raw materials for preparing the green body layer, in parts by weight, include: 13 parts of kaolin, 12 parts of potassium sodium stone powder, 8 parts of high-aluminum potassium sand, 11 parts of sodium stone powder, 10 parts of potassium sand, 16 parts of raw ore mud, 3 parts of black talc, 6 parts of polishing waste residue, 12 parts of washed sand, 8 parts of washed mud and 1 part of sodium tripolyphosphate.

[0069] S2, applying a bottom glaze on the surface of the body layer, and drying it in a drying oven at a drying temperature of 80° C. for 30 seconds to obtain a bottom glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4. Spray matte glaze on the surface of the pattern layer using a high-pressure spray glaze cabinet, dry it in a drying oven at a temperature of 150°C for 1 minute, and obtain a matte glaze layer with a thickness of 90 μm and a refractive index of 1.55; the raw materials for preparing the matte glaze, in parts by weight, include: 30 parts of high-temperature dry particles, 12 parts of medium-temperature dry particles, 6 parts of zirconium silicate, 25 parts of 9022A, 19 parts of calcium phosphate, and 8 parts of water. Among them, the sintering temperature of the high-temperature dry particles is 40°C higher than that of the medium-temperature dry particles.

[0070] The chemical composition of the high temperature dry particles, in terms of mass percentage, includes: SiO2: 50%, Al2O3: 25%, B2O3: 5%, K2O: 2%, Li2O: 2%, CaO: 6%, BaO: 4%, ZnO: 3%, ZrO2: 3%; The chemical composition of the medium-temperature dry particles, in terms of mass percentage, includes: SiO2: 52%, Al2O3: 10%, Na2O: 10%, K2O: 4%, MgO: 9%, BaO: 6%, ZnO: 7%, and SrO: 2%.

[0071] S5. A laser etching machine is used to carve a three-dimensional texture with a depth of 10 μm on the surface of the matte glaze layer.

[0072] S6, firing and forming, the firing temperature is 1180° C., and the firing time is 76 minutes, so as to obtain the ceramic tile with the gradient gloss effect.

[0073] The performance tests were conducted on the tiles of Examples 1 to 3 and Comparative Examples 1 to 10, and the test methods and standards were as follows: 1. Wear resistance: GB / T 3810.7-2016 is used to test the wear resistance: the wear of the brick surface after grinding at a specific grinding number of revolutions is observed, and it is divided into 0 to 5 levels, among which, the visible wear after 100 revolutions is level 0, the visible wear after 150 revolutions is level 1, the visible wear after 600 revolutions is level 2, the visible wear after 750 / 1500 revolutions is level 3, the visible wear after 2100 / 6000 / 12000 revolutions is level 4, and the visible wear after more than 12000 revolutions is level 5.

[0074] 2. Antifouling: Refer to the national standard GB / T 3810.14-2016 to test the antifouling performance: The antifouling performance of the brick surface treated with the surface treatment agent is tested. The test principle is to bring the pollutant (chrome green, iodine tincture and olive oil, etc.) into contact with the front of the brick and let it act for a certain period of time, then clean the brick surface according to the prescribed cleaning method, observe the changes on the brick surface to determine the brick's pollution resistance, the grades are divided into 1 to 5, and grade 5 has the best pollution resistance.

[0075] 3. Gloss: Refer to GB / T4100-2015 standard and use a photometer to measure the gloss of different positions on the brick surface at a measuring angle of 60°.

[0076] 4. Three-dimensional surface texture: Observe the brick surface with the naked eye at a distance of 0.5 meters from the brick surface at an angle of 45 degrees to see whether the surface texture has three-dimensional height differences.

[0077] The test results of Examples 1 to 3 and Comparative Examples 1 to 10 are shown in Table 1.

[0078] Table 1 As shown in Table 1, the glaze surfaces of the tiles of Examples 1 to 3 present a gradual gloss effect, with a wide range of gloss gradients. The gloss measured at an incident angle of 60° is 5 to 70 GU. Figure 1 and Figure 2 As shown, the three-dimensional texture of the glaze combined with the gloss changes makes the visual effect more three-dimensional, and the glaze has good physical properties, with wear resistance reaching level 4 and anti-fouling reaching level 5.

[0079] The high gloss glaze formula of Comparative Example 1 does not contain nano-material SiO2-coated TiO2 powder, and the physical properties of the glaze surface are reduced, and the wear resistance is reduced to level 2.

[0080] The matte glaze formula of Comparative Example 2 does not contain medium-temperature dry particles, the glaze surface temperature is high, the surface is porous, and the anti-fouling performance is reduced to level 3.

[0081] The matte glaze formula of Comparative Example 3 does not contain high-temperature dry particles, the glaze surface temperature is low, the wear resistance is level 2, which is significantly reduced, and there is no obvious change in the light perception of the glaze surface.

[0082] In Comparative Examples 4 and 5, the high-gloss glaze layer is too thin or too thick, the glaze performance is slightly weakened, and the difference in light perception is weakened.

[0083] In Comparative Examples 6 and 7, the matte glaze layer is too thin or too thick, the glaze performance is slightly weakened, and the difference in light perception is weakened.

[0084] In comparative example 8, the matte glaze layer was applied first and then the high-gloss glaze layer was applied, and the wear resistance of the glaze surface was reduced to level 2.

[0085] Comparative Examples 9 and 10 do not apply a matte glaze layer or a high-gloss glaze layer, and there is no superposition effect of the two glaze layers. There is no change in light perception on the glaze surface, and the three-dimensional effect of the surface is poor.

[0086] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a tile with a gradient gloss effect and a three-dimensional texture, characterized in that: The following steps are involved: S1, pressing the green body powder into a shape, and after drying, obtaining a green body layer; S2, applying a base glaze on the surface of the green body layer to obtain a base glaze layer; S3, inkjet printing a texture on the surface of the base glaze layer to obtain a pattern layer; S4, screen printing a high-gloss glaze on the surface of the pattern layer to obtain a high-gloss glaze layer; S5, spraying matte glaze on the surface of the high-gloss glaze layer using a high-pressure glaze spray cabinet to obtain a matte glaze layer; S6, performing laser engraving on the surface of the matte glaze layer to obtain a three-dimensional texture; S7, firing and molding, that is, obtaining the ceramic tile with a gradient gloss effect and a three-dimensional texture; The raw materials for preparing the high gloss glaze in step S4 include, by weight: 28 to 40 parts of potassium feldspar, 17 to 25 parts of quartz, 8 to 15 parts of kaolin, 10 to 16 parts of high transparent frit, 2 to 4 parts of niobium pentoxide, 7 to 14 parts of dolomite, 1 to 4 parts of zirconium silicate, 1.5 to 4 parts of perlite and 2 to 4 parts of nanomaterials; The raw materials for preparing the matte glaze in step S5 include, by weight: 30 to 45 parts of high-temperature dry particles, 8 to 12 parts of medium-temperature dry particles, 6 to 15 parts of emulsifiers, 20 to 35 parts of suspending agents, 11 to 23 parts of auxiliary agents and 8 to 13 parts of water.

2. The method for preparing a tile having a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The nano material is SiO2 coated TiO2 powder.

3. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The chemical composition of the highly transparent frit is expressed in mass percentage and includes: SiO2 60%~75%; Al2O35%~15%; B2O35%~10%; Na2O and / or K2O 10% to 20%; CaO and / or MgO 1% to 5%; ZnO 0%~5%; The chemical composition of the high-temperature dry particles, measured in mass percentage, includes: SiO250%~70%; Al2O310%~25%; B2O30%~8%; ZnO 0%~5%; ZrO20%~5%; Alkali metal oxides 2% to 10%; Alkaline earth metal oxides 5% to 15%; The chemical composition of the medium-temperature dry particles, measured in mass percentage, includes: SiO2 52%~66%; Al2O310%~12%; Na2O and / or K2O 5% to 15%; ZnO5%~7%; SrO2%~3%; Alkaline earth metal oxides 9% to 15.5%; The alkali metal oxide is at least one of Na2O, K2O and Li2O; the alkaline earth metal oxide is at least one of CaO, MgO and BaO.

4. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The thickness of the high-gloss glaze layer is 180 to 360 μm, and the refractive index of the high-gloss glaze layer is 1.68 to 1.72; the thickness of the matte glaze layer is 90 to 180 μm, and the refractive index of the matte glaze layer is 1.45 to 1.

55.

5. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The opacifier includes one or both of zirconium silicate and calcium fluoride.

6. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The auxiliary agent includes one or both of calcium phosphate and tetragonal alumina.

7. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: In step S6, a three-dimensional texture with a depth of 10 to 50 μm is engraved on the surface of the matte glaze layer.

8. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: The raw materials for preparing the green body layer include, by weight, 10 to 15 parts of kaolin, 12 to 16 parts of sodium potassium stone powder, 6 to 11 parts of high-aluminum potassium sand, 10 to 13 parts of sodium stone powder, 9 to 14 parts of potassium sand, 14 to 19 parts of raw ore mud, 2 to 5 parts of black talc, 3 to 8 parts of polishing waste residue, 9 to 14 parts of washed sand, 5 to 9 parts of washed mud and 0.8 to 1.5 parts of additives.

9. The method for preparing a tile with a gradient gloss effect and a three-dimensional texture according to claim 1, characterized in that: In step S7, the firing temperature is 1180-1225° C., and the firing time is 55-76 minutes.

10. A tile with a gradient gloss effect and a three-dimensional texture, characterized in that: The product is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Colored ceramic rock plate with texture modeling and preparation method of colored ceramic rock plate

    CN114227880A

  • Rock plate with gradient color and weaving effect and preparation method thereof

    CN114230377A

  • Ceramic tile with horseshoe pattern tile surface and preparation process of ceramic tile

    CN116161947A

  • Waxy dry granular glaze, agalmatolite ceramic tile and preparation method of agalmatolite ceramic tile

    CN117623629A